Physics beyond the Standard Model at ATLAS - Myaghov, Alexey (2008)
Summary: This report briefly reviews the potential of the ATLAS experiment to discover new phenomena beyond the Standard Model like new gauge bosons, extra dimensions and SUSY particles
Bibliografija: 14 jed
Sažetak
Keywords: Fizika elementarnih čestica -- Standardni model